2017
DOI: 10.1103/physrevb.95.094420
|View full text |Cite
|
Sign up to set email alerts
|

Single-component molecular material hosting antiferromagnetic and spin-gapped Mott subsystems

Abstract: We investigated a system based solely on a single molecular species, Cu(tmdt) 2 , accommodating d and π orbitals within the molecule.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
(28 reference statements)
0
11
0
Order By: Relevance
“…2(b). We note that the dpσ anisotropic hyperfine coupling constant, B d = 0.02 − 0.03 kOe/(μ B dpσ ) [23], is negligibly small; therefore, K aniso selectively probes the pπ spins. K aniso coincides with B π χ/2 at high temperatures; however, it rapidly deviates downward from B π χ/2 upon cooling, clearly indicating an accelerated increase in the dpσ spin contribution to χ .…”
Section: Experimental Methodsmentioning
confidence: 89%
See 3 more Smart Citations
“…2(b). We note that the dpσ anisotropic hyperfine coupling constant, B d = 0.02 − 0.03 kOe/(μ B dpσ ) [23], is negligibly small; therefore, K aniso selectively probes the pπ spins. K aniso coincides with B π χ/2 at high temperatures; however, it rapidly deviates downward from B π χ/2 upon cooling, clearly indicating an accelerated increase in the dpσ spin contribution to χ .…”
Section: Experimental Methodsmentioning
confidence: 89%
“…5(a)] and, at the lowest temperature, spread symmetrically with clear edges at ±2.1 MHz, superposed by a sharp central peak. As mentioned above, the hyperfine coupling constant of the 13 C nucleus with the pπ spin is 100-fold larger than that with the dpσ spin [20,23]; thus the spectral broadening is attributed to the pπ spins. To evaluate the size of the ordered moment, we simulated 13 C NMR powder spectra, assuming that the AF moments are flopped to arbitrary directions in the plane normal to the applied field (see Appendix A).…”
Section: Af Order Spectramentioning
confidence: 85%
See 2 more Smart Citations
“…indeed, NMR studies of Cu(tmdt) 2 found that the dpσ and pπ orbitals host antiferromagnetic and spin-gapped Mott subsystems, respectively 8,9 . For M = Ni, Pt and Zn, the dpσ orbitals lie away (upward in the former two and downward in the latter) from the two pπ orbitals located near the Fermi level 4, 10 .…”
mentioning
confidence: 99%